Implementation of Population Administration Policy on the Quality of Death Certificate Issuance Services - Deni Sudrajat; Tine Badriatin; Rudi Setiawan; Sri Sudiarti (Indonesian Journal of Social Science Research, 2021)
This study aims to determine the influence of population administration policy implementation to service quality Issuance of a death certificate in the Department of Population and Civil Registration Tasikmalaya District, which is based on the theories that are relevant to the research conducted. The method used in this research is explanatory research, which is a research-based survey. Data collection techniques used through observation, documentation, and questionnaires, while data analysis is used through multiple regression testing subsequent partial (lane) of each dimension studied (path analysis). The results of the study showed that the implementation of a policy of population administration influence the quality of service the issuance of a death certificate in the Department of Population and Civil Registration Tasikmalaya Regency is determined by the size and purpose of the policy, policy resources, characteristics or properties of entities implementing agencies, communication among relevant organizations with implementation activities, the attitude of the executive, and the environment as economic, social, political.